Marlon K. Hom. Songs of Gold Mountain: Cantonese Rhymes from San Francisco Chinatown. Berkeley: University of California Press, 1987. IX+ 322 pp. - Moncayo, Rosa Elena (Estudios de Asia y África, 1996)
-